VD_FINDINFO Décision / 2014 / 249 vom 23. Oktober 2013 - VD Tribunal cantonal (2013)
DÉPENS, INDEMNITÉ ÉQUITABLE, FRAIS DE LA PROCÉDURE, FRAIS JUDICIAIRES | 395 let. b CPP (CH), 429 al. 1 let. a CPP (CH), 429 al. 1 let. c CPP (CH)